1996
DOI: 10.1128/iai.64.11.4495-4500.1996
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and genetic analysis of the Vibrio cholerae aminopeptidase gene

Abstract: The structural gene for the Vibrio cholerae leucine aminopeptidase (lap) was cloned and sequenced. The cloned DNA fragment contained a 1,503-bp open reading frame potentially encoding a 501-amino-acid polypeptide with a calculated molecular mass of 54,442 Da. The deduced amino acid sequence of the entire protein showed high homology with the sequence of Vibrio proteolyticus leucine aminopeptidase. The residues potentially involved in binding the zinc ions were completely conserved in the V. cholerae aminopepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…For the boosting injections, 50 Wg of protease and Freund's incomplete adjuvant was used. Anti-HAP antiserum was prepared previously in our laboratory [9].…”
Section: Antiserum Preparationmentioning
confidence: 99%
“…For the boosting injections, 50 Wg of protease and Freund's incomplete adjuvant was used. Anti-HAP antiserum was prepared previously in our laboratory [9].…”
Section: Antiserum Preparationmentioning
confidence: 99%
“…Significant similarity with the amino acid sequence of this aminopeptidase was found in only two other enzymes. These were the aminopeptidases from Vibrio proteolytica [3] and V. cholerae [4], with 56.7 and 52.0 % identity respectively. V. proteolytica aminopeptidase has been studied thoroughly [5][6][7][8][9][10][11], and it belongs to a unique family of zinc-dependent proteolytic enzymes with co-catalytic metal centres [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of V. proteolytica aminopeptidase revealed that the active site consists of a metal-binding site and a well-defined hydrophobic pocket [13]. With the exception of one residue (Met-296 of apAC) [2,4], the amino acids involved in the binding of the two zinc ions and those associated with the hydrophobic pocket are highly conserved in these three aminopeptidases from different species. Therefore, it is conceivable that the catalytic mechanism of apAC is similar to those of the V. proteolytica and V. cholerae aminopeptidases.…”
Section: Introductionmentioning
confidence: 99%
“…A 3 stage PCR was designed consisting of a preliminary PCR stage followed by a thermal asymmetric interlacing (TAIL) PCR, 14,15 hemispecific PCR protocol, and concluding with a confirmatory proof reading PCR stage devised to determine the nucleotide sequence of the Flavobacterium breve-AMP gene. Alignment of the N-terminal peptide sequence of Flavobacterium breve-AMP with the peptide sequences of the bacterial leucyl aminopeptidase's of Aeromonas caviae-T64, 16 Vibrio proteolytica 17 and Vibrio cholerae 18 was initially utilized in determining highly conserved and homologous regions of the peptides.…”
Section: Cloning Of Aminopeptidase Genementioning
confidence: 99%